Dietary calcium intake and bone density among postmenopausal women: dietary calcium intake and bone mineral density among postmenopausal women in Tehran, Iran - Tajik, Esra; Mohd Shariff, Zalilah (LAP Lambert Academic Publishing, 2014)
Osteoporosis is a major public health problem and increases in women after their estrogen production decreases during menopause. Osteoporotic fracture can be an economic burden to health-care systems worldwide which eventually could lead to morbidity and mortality. This disease can be prevented and treated, but usually it remains silent until the first fracture occurs. There are many factors associated with bone mineral density among postmenopausal women while most of the studies consider two or three factors. The current study indicated several factors related to osteoporosis among postmenopausal women.